The use of board game to enhance teaching and learning on sketching free body diagram in physics / Nurulhuda Mohammad Yusoff ... [et al.] - Mohammad Yusoff, Nurulhuda; Aziz, Siti Maisarah; Mat Rosid, Salmiah Jamal; Othman, Aida; Ismail, Ismahafezi; Umar, Roslan; Muhammad Amin, Siti Noor Syuhada (UiTM Cawangan Negeri Sembilan, 2023)
The current state of education is witnessing a shift towards interactive learning experiences, moving away from the conventional approach of written essays presented through slide presentations or video stills. The term 'interactive' in the education sector encompasses a wide range of meanings, with students no longer limited to passive listening and note-taking, but instead learning through hands-on activities, internet access, and advanced technologies like Augmented Reality. The decline in the popularity of science education in recent years is largely attributed to the lack of mastery and requires a modern approach to sustain students' interest. To address this issue, a study was conducted to evaluate students' proficiency in sketching Free Body Diagram, depicting forces acting on an object, in accordance with Newton's Laws. The results revealed that students require learning aids to enhance their understanding of sketching Free Body Diagram. In response to this, a prototype of MyForce@FBD, a learning tool, has been developed with a gamification concept, combined with an Augmented Reality application, to emphasize the basic concepts of force and hands-on sketching. The primary aim of this project is to improve students' sketching skills, starting with elementary sketchings and progressing to more complex illustrations, to help them comprehend how forces act on objects according to Newton's Law. The development of such projects is crucial in diversifying learning and teaching techniques in line with the IR4.0 Education revolution.